Quantification of Pulmonary Artery Configuration after the Arterial Switch Operation: A Pilot Study - Thomas Martens; Gillian Claeys; Joachim De Groote; Meletios Kanakis; Martin Kostolny; Victor Tsang; Marina Hughes (Diagnostics, 2022)
Background: The arterial switch operation (ASO) is the preferred treatment for d-transposition of the great arteries (TGA). Freedom from reintervention is mainly determined by the performance of the arterial outflow tracts, with variable incidence of pulmonary artery stenosis (PAS), possibly related to aspects of surgical technique. This pilot study attempts to describe pulmonary artery (PA) configuration through several measurements using three-dimensional data from cardiac magnetic resonance (CMR) imaging and assesses whether PA configuration is associated with PAS. Methods: A retrospective, single-centre analysis of paediatric patients undergoing CMR after ASO. The geometry of the pulmonary arteries was compared between patients with and without PAS as judged by the CMR report. Results: Among all patients (n = 612) after ASO, 45 patients underwent CMR at a median age of 10 years (3.5–13). Twenty-two (57.9%) had PAS, categorized as mild (n = 1), moderate (n = 19) or severe (n = 2). Eighteen had stenosis on PA branches. Four had MPA stenosis. Comparison between groups with and without PAS revealed no significant differences in neo-aortic to pulmonary angle, MPA to LPA/RPA angle, or bifurcation angle. There was a significant difference in cranial displacement, with more cranial displacement in the group without PAS. However, this group was older, 10.8 (7.3–14.3) years compared to those with PAS, 6.8 (1.5–12.1). Conclusions: The spectrum of PAS after ASO is heterogenous. This study shows the feasibility of measuring PA configuration in three planes on CMR. There is no correlation between PA configuration and PAS. Therefore, other mechanisms are probably responsible for the occurrence of PAS, rather than the configuration on itself. Further multicentric studies are warranted to confirm the suggested measuring method and assessing the associations with PAS, to eventually advise surgical methodology.